Exploring psychologists' self disclosure practices and privacy management strategies on their personal Facebook profile : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Albany, New Zealand - Beaumont, Jessica (Massey University, 2016)
According to Mark Zuckerberg, founder of Facebook, the level of transparency that social networking sites has brought to the world will no longer support an individual having a personal and a professional identity; the two will become one and the same. This is a concern for those in the psychological profession, where self-disclosure of a personal nature is not only not recommended but is often considered to violate ethical principles of the profession, and could result in negative consequences for both the clients and the psychologists. This study explores how psychologists manage the balance between the self-disclosing nature of social networking sites with the need to protect their privacy online. Psychologists (n=99) from the New Zealand College of Clinical Psychologists and the New Zealand Psychological Society were asked to complete a survey indicating their self-disclosure practices and privacy management strategies on their personal Facebook profiles. Results suggest that psychologists are relatively consistent in the rules they have in place about who they share their information with and the strategies they use to protect it. Of the participants, 10% were found to have fully public disclosure practices, with the remainder having moderately or strict practices. While psychologists are engaging in self-disclosures on Facebook they appear to be doing so with some privacy protection strategies in place.